2022
DOI: 10.3390/info13030114
|View full text |Cite
|
Sign up to set email alerts
|

Awakening City: Traces of the Circadian Rhythm within the Mobile Phone Network Data

Abstract: In this study, call detail records (CDR), covering Budapest, Hungary, are processed to analyze the circadian rhythm of the subscribers. An indicator, called wake-up time, is introduced to describe the behavior of a group of subscribers. It is defined as the time when the mobile phone activity of a group rises in the morning. Its counterpart is the time when the activity falls in the evening. Inhabitant and area-based aggregation are also presented. The former is to consider the people who live in an area, whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 61 publications
(111 reference statements)
1
17
0
Order By: Relevance
“…In our earlier works, the cellphone prices were used to estimate the socioeconomic status [6,7], but the utilised cellphone price data was depreciated causing distortion in the results. In this paper, release prices of the mobile phones are gathered using Generative Pre-trained Transformer 3 (GPT-3) [8] to resolve this issue.…”
Section: Of 21mentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier works, the cellphone prices were used to estimate the socioeconomic status [6,7], but the utilised cellphone price data was depreciated causing distortion in the results. In this paper, release prices of the mobile phones are gathered using Generative Pre-trained Transformer 3 (GPT-3) [8] to resolve this issue.…”
Section: Of 21mentioning
confidence: 99%
“…During data preprocessing, they eliminated CDRs from Subscriber Identity Modules (SIMs), which did not operate in mobile phones using Type Allocation Code (TAC) databases [6]. In another work, they analysed subscribers' wake-up times and explained how it correlates with their socioeconomic status [7]. They also showed that the phone prices in the TAC database might have depreciated [7].…”
Section: Socioeconomic Status Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis demonstrated a strong positive connection between the two indicators. They also showed that the mobile phone prices in the TAC database might have depreciated [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, the commuting tendencies of the Budapest Metropolitan Area are analyzed in more detail. In [5], the temporal differences in the mobile network activity between the regions of Budapest are demonstrated, along with the typical times when a group of subscribers "wakes up" from a mobile network perspective. Some analyses regarding the length of the working hours are also presented.…”
Section: Introductionmentioning
confidence: 99%